The individual performance outcome behind e-commerce - Tam, Carlos (2020)
Tam, C., Loureiro, A., & Oliveira, T. (2020). The individual performance outcome behind e-commerce: Integrating information systems success and overall trust. Internet Research, 30(2), 439-462. [Advanced online publication on 22 october 2019]. https://doi.org/10.1108/INTR-06-2018-0262